PERAN GURU DALAM MENGEMBANGKAN KETERAMPILAN BERBICARA SISWA SDN 040450 KABANJAHE - Rahayu Damayanti Br Ginting; Yunistita Singarimbun; Nurlia Ginting (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study discusses the role of the teacher in developing students’ speaking skills in Indonesian language learning through the role-play method in Grade V of SD Negeri 040450 Kabanjahe, Academic Year 2025/2026. The main problem underlying this research is the low level of students’ speaking skills due to learning activities that tend to be monotonous and provide limited opportunities for students to actively speak. This study aims to describe the teacher’s role in guiding and facilitating students’ speaking skills, to identify the strategies applied by the teacher, and to determine the supporting and inhibiting factors in its implementation. This research employed a descriptive qualitative approach. The research subjects consisted of the Grade V homeroom teacher and 28 Grade V students. Data were collected through observation, interviews, and documentation, supported by triangulation to strengthen data validity. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results showed that the teacher performed the roles optimally as a motivator, facilitator, and evaluator. Through the role-play method, students were encouraged to participate more actively in speaking, develop dialogues, adapt to assigned roles, and express ideas orally in a more meaningful context. Students’ speaking skills in terms of pronunciation clarity, speaking fluency, content accuracy, sentence structure, and vocabulary use were categorized as good. Students’ attitudes during speaking activities and their responses toward the role-play method were also considered good. This study contributes as a reference for learning practices that emphasize active and communicative learning to develop elementary school students’ speaking skills.